2020
DOI: 10.1039/c9cp06689f
|View full text |Cite|
|
Sign up to set email alerts
|

Isomer-specific cryogenic ion vibrational spectroscopy of the D2 tagged Cs+(HNO3)(H2O)n=0–2 complexes: ion-driven enhancement of the acidic H-bond to water

Abstract: Enhancement of the acid–base interaction between HNO3 and water by a proximal Cs+ cation with cryogenic ion vibrational spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Activation of the IR-forbidden diatomic stretching transitions is attributable to polarization of, and charge transfer to, the diatomic tag by the molecular ion. This behavior and the expected relationship between transition strength and red shift (transition strength and red shift increase together) has been treated in previous work and agrees with the trends observed here. Red shifts of the H 2 stretching transitions observed in this work are summarized in Figures S5 and S6.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Activation of the IR-forbidden diatomic stretching transitions is attributable to polarization of, and charge transfer to, the diatomic tag by the molecular ion. This behavior and the expected relationship between transition strength and red shift (transition strength and red shift increase together) has been treated in previous work and agrees with the trends observed here. Red shifts of the H 2 stretching transitions observed in this work are summarized in Figures S5 and S6.…”
Section: Results and Discussionsupporting
confidence: 91%
“…This study extends an earlier report 25 that quantified the intramolecular distortions suffered by the HNO 3 molecule in the Cs + •(HNO 3 )(H 2 O) n=0−2 series. That study found that the 450 cm −1 red shift in the acidic OH stretch fundamental of the bare nitric acid HNO 3 ( bare ν OH a in Figure 1A) upon formation of the neutral HNO 3 (H 2 O) van der Waals complex 26 is further displaced by 459 cm −1 when the Cs + cation binds to the acid's −NO 2 group to form the ternary Cs + •(HNO 3 )H 2 O cationic cluster.…”
supporting
confidence: 88%
“…The oscillator strength derived from the water-bound OH group of the acid (hereafter denoted OH a ), appears as a very intense envelope (ν OH a–w in Figure B) with a progression in soft mode combination bands (blue in Figure B above the OH stretching fundamental at 2641 cm –1 ). In that paper, it was noted that the addition of a second water molecule retains this ternary sandwich structure as the second water adopts a position in the first hydration shell of the Cs + ion. Here we follow the structural evolution of the acid during sequential hydration in the series Cs + ·HNO 3 (H 2 O) n =3–11 , which explores the size range through completion of the first hydration shell around Cs + .…”
mentioning
confidence: 99%
“…However, correlating measured detachment energies with a particular ion pair motif, specifically, when multiple isomers are present, is challenging. More detailed structural information can be extracted using infrared photodissociation (IRPD) spectroscopy, in particular, when performed isomer‐specifically [12] . So far, IRPD studies on microhydrated cluster ions have mainly focused on the characterization of CIPs [13] .…”
Section: Figurementioning
confidence: 99%